1997
DOI: 10.1161/01.atv.17.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Uptake by J774 Macrophages of Very-Low-Density Lipoproteins Isolated From ApoE-Deficient Mice Is Mediated by a Distinct Receptor and Stimulated by Lipoprotein Lipase

Abstract: Apolipoprotein (apo) E-deficient mice display marked accumulation in the plasma of VLDL deficient in both apoE and apoB100 but containing apoB48, apoA-I, apoCs, and apoA-IV. Since apoE-deficient mice develop severe atherosclerotic lesions with lipid-laden macrophages, we reasoned that the uptake of lipoproteins by intimal macrophages can take place in the absence of both apoE and apoB100. To get more insight into the mechanism of foam cell formation in apoE-deficient mice, we measured the interaction of VLDL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Recently, a specific and saturable receptor activity for ␤-VLDL derived from apoE-deficient mice was characterized in a murine M cell line. 55 Binding of ␤-VLDL to this receptor is not competed for by LDL or by AcLDL but is competed for by normal VLDL. 55 Recently, hepatic SR-A was overexpressed in transgenic mice to investigate the functional role of these site-specific receptors in clearing potentially atherogenic lipoproteins.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, a specific and saturable receptor activity for ␤-VLDL derived from apoE-deficient mice was characterized in a murine M cell line. 55 Binding of ␤-VLDL to this receptor is not competed for by LDL or by AcLDL but is competed for by normal VLDL. 55 Recently, hepatic SR-A was overexpressed in transgenic mice to investigate the functional role of these site-specific receptors in clearing potentially atherogenic lipoproteins.…”
Section: Discussionmentioning
confidence: 98%
“…55 Binding of ␤-VLDL to this receptor is not competed for by LDL or by AcLDL but is competed for by normal VLDL. 55 Recently, hepatic SR-A was overexpressed in transgenic mice to investigate the functional role of these site-specific receptors in clearing potentially atherogenic lipoproteins. 56 The mouse transferrin promoter targeted expression of the bovine SR-A type I to murine liver.…”
Section: Discussionmentioning
confidence: 98%
“…AcLDL was prepared as described by Goldstein et al (29). bVLDL was isolated from cholesterol-fed apoE-null mice (30).…”
Section: Reagentsmentioning
confidence: 99%
“…9,11,30 Arterial-wall macrophages loaded with large amounts of cholesteryl ester (macrophage foam cells) are thought to play a major role throughout atherogenesis. [31][32][33][34][35][36][37][38] Studies with cultured macrophages have revealed that massive cholesteryl ester accumulation cannot simply be induced by many types of monomeric lipoproteins that are thought to be atherogenic, such as native LDL, 39 certain forms of oxidized LDL, 40 -43 and lipoproteins from atherosclerotic apolipoprotein E-knockout (E0) mice 44 (S.M. et al, unpublished data, 1999).…”
mentioning
confidence: 99%